Digital implementation of a new PWM switching scheme for cascaded multilevel voltage source inverter - Salam, Zainal; Aziz, J.; Ahmed, S. S. (Faculty of Electrical Engineering, 2005)
This work proposes a new switching scheme for the cascaded multilevel inverter that can be suitably implemented using digital technique. Unlike other schemes, the proposed method is based on the symmetric regular sampling unipolar PWM with a single carrier and multiple modulating signals. Non-transcendental trigonometric equations that define the switching instants of the multilevel inverter are derived. This algorithm is implemented digitally using a low-cost fixedpoint microcontroller on an experimental five-level cascaded inverter test-rig.